L'Amérique Latine sous le regard des frères Grandidier, explorateurs scientifiques polyvalents (1857-1859) - Jehanne-Emmanuelle Monnier (Les Cahiers ALHIM)
This article deals with the fieldwork of relatively unknown French scientists of the mid-nineteenth century, the Grandidier brothers, at the end of the golden age of European exploration in South America. The study also refers to the great naturalist figures who preceded the Grandidier brothers at the beginning of the century, from whom they draw inspiration. The Grandidier's travel narrative also offers a first-hand account of the political and social situation in Latin American countries following independence, as well as on the health conditions of the trip.